Persepsi Editor Melayu Terhadap Pengamal Perhubungan Awan di Malaysia - Mohd Yahya Mohamed Ariffin; Md Sidin Ahmad Ishak (Akademi Pengajian Melayu, Universiti Malaya, 2024)
Media relation is an important aspect in organizational communication strategy. Thus, it is highly critical for public relations practitioners to build an effective relationship with media personalities. This study is focusing on media relations practices in Malaysia with the attention to Malay editors‟ perception on public relations practitioners. In-depth interviews are conducted to study the opinions of Malays editors from two media organizations namely Berita Harian and TV3 on public relation practitioners. This study has found that public relations practitioners are generally viewed by the Malays editors as intelligent, honest, trustworthy, ethical, virtuous and fair sources. However, the less experienced practitioners as well as the non-consultant are perceived less positively. The study asserts that the Malay editors‟ perception influences media relations and that good relationship needs to be strengthened for more efficient public relations undertaking.